EFFECTIVENESS FUND VILLAGE IMPROVEMENT IN THE SEA IN THE VILLAGE DEVELOPMENT DISTRICT PINELENG MINAHASA - Sumolang, Ayrton; Posumah, Johnny Hanny; Kolondam, Helly (JURNAL ADMINISTRASI PUBLIK, 2016)
This research thesis preparation with a view to obtaining a bachelor's degree in social and political science faculty, that there are problems in the process and in the implementation of increased development funds through the village in the Village District of Pineleng Minahasa Sea. Researchers saw that the lack of cooperation between government and community development improvement. In stepping up development in the Village Sea through the village fund or assistance from the central government to village aspired to achieve a prosperous society and is able to manage the autonomy in the village in accordance with the laws that exist to growth and change in a planned and conscious taken by a country and nation toward modernity in order to develop the nation. But what happens the public still was not satisfied with the performance of the government's development, as seen from the problems that occur through the government's development is still lacking precise targets and a lack of consistency on the part of the government regarding village development forum that governments actually took the benchmark through deliberation village, which has been set in the deliberations when in fact it should be done instead of carrying out construction just see where that becomes personal or group interests to seek opportunities through the village fund for rural development and implicated in political elements. Keywords: effectiveness of village funds, increased development.